Novejša spoznanja o razvoju otrokove risbe - Slatinšek-Mlakar, Aleksandra (Revija za elementarno izobraževanje, 2009)
Recent findings about the development of children's drawings. n this article we present the results of a research called "A child at play". The purpose of this research was to find out what the differences are among pupils who are aged between 6 and 9. We were interested in the differences in the number of people and toys or games that were depicted in the drawings among pupils of different ages. There were 174 Slovene pupils from the 1st to 4th grades of primary school included in the research, namely 103 boys and 71 girls. We conducted the research on the basis of previously known facts about developmental rules, meaning the levels of development in a children's drawings, the developmental process in artistic expression of children between the ages of 6 and 9, and the different influences on the reflection of a child's drawing. The results obtained in the research have confirmed previously known facts about the development of childrens' drawings, which are described in the theoretical part of the paper. According to our findings on the development of childrens' drawings and in relation to the tasks of art education in the first four grades of primary school (stated in the theoretical part) we were able to interpret the differences according to the gender and age of the pupils. We found out that gender-stereotypical differences in the choice of a favourite toy is apparent. There is a difference in the choice of a toy, which is conditioned by the childrens' age, but not on the level of statistical characteristics. However, it is important to emphasize the findings of the authors Marjanovič Umek in Lešnik Musek (2001), who wrote that childrens' drawings, regardless of the level, are not connected to the age-level but to the mixing of perception, motion, thinking and the child's own interests and motivation.